2019
DOI: 10.1128/aac.01842-18
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Linezolid-Resistant Clinical Isolates of Mycobacterium abscessus

Abstract: A total of 194 Mycobacterium abscessus isolates were collected from patients, and the whole genomes were sequenced. Eighty-five (43.8%) isolates showed linezolid (LZD) resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Accumulated evidence suggests that linezolid possesses elevated anti- M. abscessus activity. Recently, we reported the high activity expressed by linezolid in vitro against clinical M. abscessus isolates collected from patients with lung diseases (10). A study conducted using a Drosophila melanogaster -infection model demonstrated the anti- M. abscessus activity of linezolid in vivo (23); the successful use of linezolid in treating clinical M. abscessus infections was also reported (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated evidence suggests that linezolid possesses elevated anti- M. abscessus activity. Recently, we reported the high activity expressed by linezolid in vitro against clinical M. abscessus isolates collected from patients with lung diseases (10). A study conducted using a Drosophila melanogaster -infection model demonstrated the anti- M. abscessus activity of linezolid in vivo (23); the successful use of linezolid in treating clinical M. abscessus infections was also reported (24).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported a series of studies demonstrating the antibiotic susceptibility of clinical M. abscessus isolates and the treatment outcomes of patients diagnosed with M. abscessus pulmonary disease (1013). A number of cases accumulated during the course of these studies dealt with the long-term treatment with antibiotics, including linezolid and tigecycline; the adverse effects of antibiotic treatment were well documented.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of thiacetazone analogs, mutations in the TetR repressor MAB_4384 led to upregulation of the adjacent genes encoding an MmpS-MmpL efflux pump system (35,36). Increased expression of MAB_4746, encoding a member of the MmpL family, was also reported recently in LNZ-resistant isolates (37). In the case of CFZ, where CFZ-resistant strains demonstrated cross-resistance to BDQ (29), whole-genome sequencing analyses of the in vitro-selected resistors uncovered point mutations in MAB_2299c (29), a member of the TetR family of transcriptional regulators, representing the most abundant family of regulators in mycobacteria.…”
Section: Discussionmentioning
confidence: 55%
“…One hundred and nighty-four clinical isolates were collected as described previously from the sputum and bronchoalveolar lavage fluid samples of patients with lung infections in Shanghai Pulmonary Hospital. 11,14 Isolates were initially screened for non-tuberculosis mycobacteria by growth in MGIT960 culture medium and resistance to p-nitrobenzoic acid. M. abscessus was identified by sequencing the rpoB and erm(41) genes.…”
Section: Bacteriamentioning
confidence: 99%